1991
DOI: 10.1001/archsurg.1991.01410340037006
|View full text |Cite
|
Sign up to set email alerts
|

A Current Analysis of Primary Lymphoma of the Thyroid

Abstract: Over a 9-year period ending in May 1990, 27 patients with histologically proved thyroid lymphoma were assessed and treated. There were 24 female and three male patients with a median age of 67 years at the time of diagnosis (age range, 39 to 85 years). The usual presentation was that of a rapidly enlarging neck mass. Incisional biopsy was the diagnostic procedure of choice; however, nine of 27 patients underwent diagnostic partial or total thyroidectomy based on a preoperative impression of thyroid carcinoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2
7

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 19 publications
4
32
2
7
Order By: Relevance
“…Although some investigators question any special relationship between thyroid and gastrointestinal lymphoma (19), others have reported that relapse after treatment of thyroid lymphomas is frequently located in the gastrointestinal tract (12,20,21), as was also observed in our study. Most relapses seem to occur within the first 2 years after diagnosis (6,7,9,10,22).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although some investigators question any special relationship between thyroid and gastrointestinal lymphoma (19), others have reported that relapse after treatment of thyroid lymphomas is frequently located in the gastrointestinal tract (12,20,21), as was also observed in our study. Most relapses seem to occur within the first 2 years after diagnosis (6,7,9,10,22).…”
Section: Discussionsupporting
confidence: 83%
“…Most relapses seem to occur within the first 2 years after diagnosis (6,7,9,10,22). Late relapses have, however, also been reported (11,12). Lymphomas arising from MALT tend to remain localized until late in the course of the disease (1 5 , 16).…”
Section: Discussionmentioning
confidence: 99%
“…5-year survival of 70% to 80% (132,134,135). In one study, nonrandomized comparisons showed longer relapse-free survival for combination therapy than for radiotherapy (134), but another study found no difference between these two forms of treatment (132).…”
Section: Lymphoma In Wuldejw's Ringmentioning
confidence: 99%
“…that stages 11-IV should be treated by primary chemotherapy, and if complete remission is not achieved or if the disease is bulky, it should be followed by radiotherapy (128,135) or combination therapy if the patient's condition permits (131,133,134);…”
Section: The Literature Review S H O~:~mentioning
confidence: 99%
“…Almost all patients with these forms of thyroid lymphoma have a history of Hashimoto's thyroiditis. The five year survival rate for patients with thyroid lymphoma ranges from 10-35% in cases with unfavourable histology to 70% in those with favourable histology (4,5). Mediastinal involvement and performance status are important prognostic factors influencing relapse free survival and overall survival(6).…”
Section: Introductionmentioning
confidence: 99%